Optimization of bioconversion of R-(+)-limonene to R-(+)-α-terpineol by fungi in emulsion system using response surface methodology - Mirpour, Mirsasan (2011)
R-(+)-limonene is a non expensive by product of the citrus industry and it is a potential starting compound for bioconversion to fine chemicals. Chemical synthesis was used for α-terpineol production from limonene, but in this process unwanted isomers or substances were produced and generated large amounts of waste. In this study, a new method of bioconversion of R-(+)-Limonene to R-(+)-α-terpineol by seven fungi was investigated in emulsion systems which were prepared by mixing oil, Tween 80 and Potato Dextrose Broth (PDB). R-(+)-limonene was dissolved in oil phase and fungi were added into an aqueous phase. Optimization study for the best emulsion system stability was done by Design Expert 7 for three oils; decane, cyclohexane and tetradecane. The fungi were adapted 10 times to obtain strong fungi before bioconversion study. The α-terpineol yield was extracted by hexane and subsequently quantified by GC-FID. After 72 hours of bioconversion reaction using adapted fungi with 1% (w/v) R-(+)-limonene, 30% decane (v/v) and 1% tween 80 (w/v) in emulsion system at desired temperature and 160 rpm, the best yields were 176, 31.2, 29.6, 107.1, 96.6, 141.7 and 402.4 mg/100 ml for A. terreus ATCC 10029, A. niger ATCC 200345, F. oxysporum ATCC 11137, F. oxysporum CBS 620.87, P. purpurogenome PTCC 5212, P. digitatum ATCC 201167 and A. niger K8 respectively. After media components optimization that affects the fungal growth (carbon and nitrogen sources), the bioconversions were again tested by seven fungi. Final yields were 701, 133.1, 71.8, 239.6, 155.9, 349.2, and 584.1 mg/100 ml for A. terreus ATCC 10029, A. niger ATCC 200345, F. oxysporum ATCC 11137, F. oxysporum CBS 620.87, P. purpurogenome PTCC 5212, P. digitatum ATCC 201167 and A. niger K8 respectively. Optimization of bioconversion study was carried out only for the best fungus (A. terreus ATCC 10029) that gave the highest yield in a shake flask and 2L bioreactor. After optimization of the bioconversion parameters, the best yield of α-terpinel was 812 mg/100 ml for A. terreus ATCC 10029 using a shake flask. This result is about three times higher than the previously reported value (3.2 gm/l). The bioconversion studies were also carried out in emulsion systems using cyclohexane and tetradecane under the optimum conditions. The best yield using cyclohexane was 133 mg/100 ml for A. terreus ATCC 10029 and the best yield for tetradecane systems was 670 mg/100ml for Asp. niger K8. Effects of different percentage of oil phase (10%, 20% and 30% of decane, cyclohexane and tetradecane) on yields were also evaluated and it was found that the best oil for bioconversion of R-(+)-limonene to R-(+)-α-terpineol was 30% decane. Using emulsion system for bioconversion is feasible because it provides a good medium for direct interaction between fungi and substrate. Using decane (Log PO/W: 6.25) as oil phase in emulsion help to decrease limonene (Log PO/W): 4.8) toxicity toward fungi. Terpineol yields were increased after adaptation of fungi by limonene and optimization of media components. Optimization of bioconversion parameters provided new condition for A. terreus to produce more terpineol. Two another oils, cyclohexane (Log PO/W: 3.4) and tetradecane (Log PO/W: 8.19) showed decrease in yield, suggesting that toxicity is a one of important parameters for bioconversion of limonene.